2022
DOI: 10.3390/curroncol29030128
|View full text |Cite
|
Sign up to set email alerts
|

The Serious Illness Care Program in Oncology: Evidence, Real-World Implementation and Ongoing Barriers

Abstract: The Serious Illness Care Program (SICP), designed by Ariadne Labs, is a multicomponent intervention to improve conversations about values and goals for patients with a life-limiting illness. In oncology, implementation of the SICP achieved more, earlier, and better-quality conversations and reduced anxiety and depression among patients with advanced cancer. In this commentary, we describe the SICP, including results from the cluster-randomized trial, provide examples of real-world implementation of this progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Still, as evidenced by our qualitative data, there is a great interest in other types of tools such as cheatsheets and EHR embedded tools. The findings are further corroborated by research conducted in other settings, where tools supplementing the SICG (e.g., SIC reminders, behavioural nudges) emerged as crucial elements in facilitating successful implementation (59)(60)(61)(62). Consequently, future interventions adapting the SICP to a primary care context should prioritize equipping PHCPs with a wider range of tools beyond the SICG.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Still, as evidenced by our qualitative data, there is a great interest in other types of tools such as cheatsheets and EHR embedded tools. The findings are further corroborated by research conducted in other settings, where tools supplementing the SICG (e.g., SIC reminders, behavioural nudges) emerged as crucial elements in facilitating successful implementation (59)(60)(61)(62). Consequently, future interventions adapting the SICP to a primary care context should prioritize equipping PHCPs with a wider range of tools beyond the SICG.…”
Section: Discussionsupporting
confidence: 58%
“…This finding highlights a critical obstacle to large scale interventions: balancing the need for standardized content across diverse clinical contexts with the need to ensure adaptability to each practice’s specific needs (6769). However, this limitation, combined with a process evaluation, enabled the identification of key SICP components critical for maintaining and replicating its effectiveness (5, 6, 59, 60). As Konnyu et al emphasize, mapping the potential for adaptation and intervention based on behavior change techniques is crucial for identifying potential gaps and optimizing interventions accordingly (70).…”
Section: Discussionmentioning
confidence: 99%
“… 32 In an outpatient oncology clinic at the Tom Baker Cancer Centre in Canada, implementation led to increased documentation of SICs at postintervention and documentation of 93% of conversations in the electronic medical record. 32 , 33 At the Abramson Cancer Center in Pennsylvania, the majority of patients (90%) reported that the SIC was worthwhile, with 55% reporting that the conversation increased their understanding of their future health, 42% reporting increased sense of control over future medical decisions, 58% reporting increased closeness with their physician, and 42% reporting greater hopefulness about quality of life. 32 , 34 Routine implementation of the SICP for older patients with AML or MDS may lead to increased SIC documentation, improvement in patient knowledge, and may promote patient hope and positivity.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 At the Abramson Cancer Center in Pennsylvania, the majority of patients (90%) reported that the SIC was worthwhile, with 55% reporting that the conversation increased their understanding of their future health, 42% reporting increased sense of control over future medical decisions, 58% reporting increased closeness with their physician, and 42% reporting greater hopefulness about quality of life. 32 , 34 Routine implementation of the SICP for older patients with AML or MDS may lead to increased SIC documentation, improvement in patient knowledge, and may promote patient hope and positivity. A single-arm pilot study is currently ongoing to evaluate the feasibility of the SICP for older patients with AML or MDS ( clinicaltrials.gov identifier: NCT04745676 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physicians now initiate conversations about serious illness earlier with their patients, and they also continue these conversations throughout the clinical process (Back et al, 2009). This procedure has led to reduced anxiety and depression in some patients (Karim et al, 2022)-yet, the clinicians themselves still find it hard to discuss patients' prognoses and respond to their emotions (Geerse et al, 2019). Against this background, it is justified to question whether breaking bad news is all about delivering emotionally proper communication.…”
Section: Breaking Bad News As Communication Skillsmentioning
confidence: 99%